Aprendizagem da docência possibilitada pela mediação de um processo de coordenação pedagógica construtivo-colaborativo, tendo a TV comercial como suporte para a formação de cidadãos críticos - Lourenço, Roberta Bezerra de Menezes Reiff (Universidade Federal de São Carlos, 2004)
The driving force of this Doctorate degree work was the alert presented by the results of the Master of Science work (Reiff-Lourenço, 1999) that pointed to the vital importance of the professor who performs the task of conducting discussions and considerations about the critical-pedagogical analysis with regard to the use of the TV in school, to question it and to allow students to come to their own conclusions. Thus, I drove my attention to the way that the continuous formation is processed and studied this process within a constructive-collaborative methodology. In the school where I work as Pedagogic Coordinator, I created a special schedule for the construction of a new practice associated to the use of the TV in the classroom. Only interested professors participated in this practice. I took over the researching/coordinating function and thus, the Special Group was created based on the collaborative work. I wrote under the perspective of a Pedagogue who performs the Pedagogical Coordinator function, interferes on reality and produces knowledge. The work intended to respond to the following research question: What professional learning occurs to a group of professors who work in a constructive-collaborative pedagogical coordination process that uses the Commercial TV as support for the formation of critical citizens? The theoretical basis for the intervention = investigation is part of my Master of Science Dissertation that was utilized as supporting material written and as transparencies read, studied, analyzed and discussed with other professors during the Doctorate degree process. This material was the base of the construction of new pedagogical practices, dealing with the topic School, Television and Critical Formation including the following aspects: what forming a critical citizen is; what is the relation between television and critical formation; how television emerged and developed in Brazil; which types of television networks are available; to what groups they belong to; what are they interested in; how television has influenced and has been influenced by history since its emergence until the current days; what television viewers search when they turn the TV on; what is the objective of the Mass Culture; what is the role of the advertisement in the Mass Culture. Finally, this work intended to study in which ways the television could contribute for the citizen to be involved with reality and how the dialogue could contribute for the relation school, television and critical formation. The Collaborative Work was vital for the Special Group to be strengthened in order to work the criticism of the own practice. Through the collaborative work the participants helped each other, exchanged ideas, doubts and experiences. Professors should experiment, as apprentices, the type of instruction that the educational reforms promote. Through the Teaching and Apprenticeship Experiences the professors experienced the TV critical-pedagogical utilization as apprentices and concurrently, produced knowledge. Finally, as researcher/coordinator and through this intervention ⇔ investigation experience in addition to the literature studied, I could notice how important the role of the pedagogical coordinator is, above all in the continuous formation process of the group coordinated. This professional is responsible for providing opportunities for professors/apprentices to develop meanings and to construct a critical thought. The coordinator should be theoretical and methodological support, present emotional balance, encourage the professors missions, provide study, discussion and experiences exchange environments and always invest in the collaborative work in order to construct along with the group, the content of what to teach with the clearness of the social function of the school. The experience revealed to be successful and indicates the compromise of including the critical-pedagogical use of the Commercial TV in the political-pedagogical project of the mentioned school and to extend this experience to other schools, especially those from the public net.
Keywords: Educação; Aprendizagem profissional da docência; Televisão comercial - formação crítica; Coordenação pedagógica; CIENCIAS HUMANAS::EDUCACAO